2021
DOI: 10.1016/j.jvs.2021.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormones in men with abdominal aortic aneurysm

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
0
16
1
Order By: Relevance
“…When plasma DHEA, androstenedione, testosterone, and SHBG (all by immunoassay) were addressed in 37 male AAA cases and 91 healthy controls, SHBG but not sex steroids were found to be lower in cases ( 23 ). Contrasting with our findings, Villard et al recently reported a higher frequency of detectable levels of estradiol and progesterone in men with AAA, and lower testosterone in univariate models ( 24 ). While the setting of this study was a similarly sized case-control study of Swedish 65-year-old men recruited at AAA screening, Villard et al used immunoassays with low sensitivity, where 45% and 49% of the control men had estradiol and progesterone levels below the working range of the assay.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…When plasma DHEA, androstenedione, testosterone, and SHBG (all by immunoassay) were addressed in 37 male AAA cases and 91 healthy controls, SHBG but not sex steroids were found to be lower in cases ( 23 ). Contrasting with our findings, Villard et al recently reported a higher frequency of detectable levels of estradiol and progesterone in men with AAA, and lower testosterone in univariate models ( 24 ). While the setting of this study was a similarly sized case-control study of Swedish 65-year-old men recruited at AAA screening, Villard et al used immunoassays with low sensitivity, where 45% and 49% of the control men had estradiol and progesterone levels below the working range of the assay.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, a major finding in the present study was that the impact of low estradiol and low progesterone on AAA prediction was additive. Serum estradiol has previously been reported to associate positively with atherosclerosis and cardiovascular outcomes in men, but similar to Villard et al ( 24 ), most of these studies have used immune-based techniques with questionable specificity in the lower range ( 27 ). By contrast, low levels of estradiol assessed by mass spectrometry predict mortality in elderly men ( 33 ).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…As the condition primarily affects men, testosterone has been thought to attribute to AAA as demonstrated in murine studies with male mice ( 68 , 69 ), and even in female mice administered testosterone as neonates ( 61 ). However, a recent case-control study comparing 65-year old men with and without AAA found that higher oestrogen, higher progesterone and lower testosterone levels were associated with AAA ( 170 ). The association of low testosterone levels with AAA is in line with an earlier clinical and murine study ( 70 , 77 ).…”
Section: Discussionmentioning
confidence: 99%